La corruption dans l’approche économique - Gola, Jan (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The article refers to corruption in economic terms. Above all, it characterizes the influence of corruption on economy and its effects. Particular attention was paid to the impact of corruption on the loss of confidence in public institutions. Furthermore, it describes two situations relating to the pathology in economic terms, namely the cases of a constant and variable supply
Keywords: corruption; economy; pathology of the economic life